1990
DOI: 10.1111/j.2044-835x.1990.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrative story telling in autism and Down's syndrome

Abstract: The present study investigated the ability of high functioning verbal children and adolescents with autism or Down's syndrome to tell a story to a listener. Sixteen subjects with autism and 16 with Down's syndrome (DS), matched on verbal mental age, watched a short puppet show or video sketch and were then asked to tell the story to a listener and answer follow-up questions. The majority of both groups were able to produce recognizable, though primitive, narratives. The groups did not differ in general story c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(109 citation statements)
references
References 13 publications
4
102
2
1
Order By: Relevance
“…Studies comparing children with ASD and those with typical development (TD), with groups matched on language and cognitive abilities, report minimal quantitative differences in narrative length and syntactic complexity but deficits in organization and cohesiveness (Diehl et al, 2006;Tager-Flusberg & Sullivan, 1995). Narratives in ASD tend to lack coherent global organization (Baron- Cohen, Leslie, & Frith, 1986;Loveland, McEvoy, Tunali, & Kelley, 1990;Suh et al, 2014), with fewer causal connections between story events (cohesion) and reduced communication of story "gist" (Diehl et al, 2006).…”
Section: Narratives In Asdmentioning
confidence: 99%
“…Studies comparing children with ASD and those with typical development (TD), with groups matched on language and cognitive abilities, report minimal quantitative differences in narrative length and syntactic complexity but deficits in organization and cohesiveness (Diehl et al, 2006;Tager-Flusberg & Sullivan, 1995). Narratives in ASD tend to lack coherent global organization (Baron- Cohen, Leslie, & Frith, 1986;Loveland, McEvoy, Tunali, & Kelley, 1990;Suh et al, 2014), with fewer causal connections between story events (cohesion) and reduced communication of story "gist" (Diehl et al, 2006).…”
Section: Narratives In Asdmentioning
confidence: 99%
“…Baron-Cohen, Leslie and Frith (1986) were the first to show that, compared to control subjects, children with autism provided fewer mental state terms in their narratives for a sequence of pictures depicting a simple false belief scenario. In a more detailed study, Loveland and her colleagues asked their subjects to retell a story presented in the form of a puppet show or video sketch (Loveland, McEvoy, Tunali, & Kelley, 1990). The children with autism were less able than controls to consider their listener's needs and produced more bizarre or inappropriate utterances.…”
Section: Theory Of Mind and Language/communication Deficits In Autismmentioning
confidence: 99%
“…Expert manual analysis of conversations and narratives of individuals with ASD has shown that children and teenagers with autism include significantly more bizarre and irrelevant content in their narratives (Loveland et al, 1990;Losh and Capps, 2003) and introduce more abrupt topic changes in their conversations (Lam et al, 2012) than their typically developing peers. Automatic detection of poor topic maintenance has also been explored using techniques originally developed for information extraction (Rouhizadeh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%